VESSEL WALL STIFFNESS IN ARTERIAL HYPERTENSION AND OPPORTUNITIES FOR ITS MODULATION - L. L. Kirichenko; S. V. Gatsura; A. N. Golosova; Zh. Yu. Dvoryanchikova; E. A. Ulyanova; K. M. Chuprikova (Кардиоваскулярная терапия и профилактика)
Arterial hypertension (AH) is a serious medical and social problem due to its complications leading to disability. Recently, there is a lot of attention paid to markers evaluation for cardiovascular pathology — endothelial dysfunction,  arteries  elasticity decline,  increased  pulse  wave velocity (vascular  wall stiffness)  and  studying  of  an  influence  of  various antihypertension  treatments. Current  article  focuses  on  the  modern influences on remodeling of vessel wall in AH and opportunities  of its pharmacological   correction   with  angiotensine   converting  enzyme inhibitors, calcium channel blockers and beta-blockers as monotherapy and combination.